2013
DOI: 10.1637/10380-92112-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Development, Application, and Results of Routine Monitoring of Marek's Disease Virus in Broiler House Dust Using Real-Time Quantitative PCR

Abstract: Results are presented from four studies between 2002 and 2011 into the feasibility of routinely monitoring Marek's disease virus serotype 1 (MDV-1) in broiler house dust using real-time quantitative PCR (qPCR) measurement. Study 1 on two farms showed that detection of MDV-1 occurred earlier on average in dust samples tested using qPCR than standard PCR and in spleen samples from five birds per shed assayed for MDV-1 by qPCR or standard PCR. DNA quality following extraction from dust had no effect on detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 26 publications
3
36
1
2
Order By: Relevance
“…The results of our STL analysis showed that MD dynamics fluctuated within years, with relatively high rates in the winter/fall and relatively low rates in the spring/summer, consistent with previous studies (Witter 1996; Walkden-Brown et al 2013). Preliminary analysis also revealed that these fluctuations closely matched a sine curve.…”
Section: Methodssupporting
confidence: 91%
“…The results of our STL analysis showed that MD dynamics fluctuated within years, with relatively high rates in the winter/fall and relatively low rates in the spring/summer, consistent with previous studies (Witter 1996; Walkden-Brown et al 2013). Preliminary analysis also revealed that these fluctuations closely matched a sine curve.…”
Section: Methodssupporting
confidence: 91%
“…Yet the ecology of MDV is poorly understood. This is perhaps most clearly exemplified by the conventional wisdom that the virus is ubiquitously found on industrialized poultry farms (Office International des-Epizooties, 2010; Dunn, 2013), despite recent surveillance data suggesting that the virus may not be present on a large fraction of farms (Groves et al, 2008; Wajid et al, 2013; Walkden-Brown et al, 2013; Bettridge et al, 2014; Kennedy et al, 2015b, 2017; Ralapanawe et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The concentration of MDV in dust can vary several orders of magnitude between farms and within farms over time (Walkden-Brown et al, 2013; Kennedy et al, 2017). The underlying cause of this variation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Another avian herpesvirus, gallid herpesvirus 2 (GaHV-2) or Marek's disease virus (MDV), is the causative agent of Marek's disease and is also transmitted by inhalation of infective material. For this virus, routine monitoring of large flocks based on quantitative PCR (qPCR) determination of MDV viral load in poultry house dust samples has been developed as a useful disease monitoring tool (Walkden-Brown et al, 2013). This method may be useful for other avian viral pathogens such as ILTV.…”
Section: Introductionmentioning
confidence: 99%